Successful Removal of a Penile Constriction Ring in a 14-Year-Old Male - Timothy K. Suttle; Blake Palmer; Jonathan E. Heinlen; Christopher C. Roth; William G. Reiner; Dominic Frimberger (Advances in Urology)
Penile strangulation is a rarely described medical emergency, especially in the adolescent population. This case demonstrates the successful removal of a constricting metal ring from the penis of a 14-year-old male with a diamond blade equipped orthopedic oscillating saw while under ketamine anesthesia in the emergency department.